Comparison of Two Solutions of Regeneration Circuits for Tramcars - Rankis, I.; Ribickis, L.; Vitols, A. (Elektronika ir Elektrotechnika, 2006)
In the following paper are presented comparison of two solution variants for tramcars T3. There are presented results obtained form computer simulations and two principal schemes of both solutions. Also there are presented results obtained from data array and analysis of them, too. 6 characteristics of simulation of these two schemes are showed, too. Then equations with normalized parameters are presented, what is very important for clear understanding and working principles of both schemes from absolute point of view. Then there are presented characteristics that are obtained from equations with normalized parameters. Il. 11, bibl. 3 (in English; summaries in English, Russian and Lithuanian).